A Simple and Appropriate Dietary Scoring Method for Assessing Nutritional Quality of the Diet of Pregnant Women and Toddler - . Hardinsyah; Meitycorfrida Mailoa; Netti Herawati (Media Gizi dan Keluarga, 2000)
The objective of this study was to identify a simple and appropriate dietary scoring method for assessing nutritional quality of the diet of pregnant women and toddler. For this purpose, two sets of food intake data were analyzed. The first data set was the food intake data of pregnant women, which consisted of 150 pregnant women (3-8 month of pregnancy) of East Bogor, and the second data set was the food intake data of toddler which consisted of 191 toddlers (1-3 years) of rural West Java. Four simple dietary scoring methods were developed based on a dietary scoring system of the five major food groups (cereals, meats, vegetables, fruit and milk) and the six major food groups (cereals, meat, legumes, vegetables, fruit and milk). Nutritional quality of the diet (NQ) which was defined as the mean nutrient adequacy of eight nutrients was considered as the gold standard for analysing the most appropriate dietary scoring method. Correlation and dummy regression was applied for this analysis. The results showed that each of the dietary scoring method developed was significantly correlated with the NQ with correlation coefficients ranging from 0.58 to 0.80. The most appropriate and simplest dietary scoring method for assessing the NQ of pregnant women and toddlers was the dietary scoring method developed based on the six major food groups and applying three categorical levels of dietary score (0, 1,2.).